2016
DOI: 10.1093/infdis/jiw540
|View full text |Cite|
|
Sign up to set email alerts
|

Blood Gene Signatures of Chagas Cardiomyopathy With or Without Ventricular Dysfunction

Abstract: Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, affects 7 million people in Latin American areas of endemicity. About 30% of infected patients will develop chronic Chagas cardiomyopathy (CCC), an inflammatory cardiomyopathy characterized by hypertrophy, fibrosis, and myocarditis. Further studies are necessary to understand the molecular mechanisms of disease progression. Transcriptome analysis has been increasingly used to identify molecular changes associated with disease outcomes. We thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
2
25
0
5
Order By: Relevance
“…Histopathological analysis of hearts from patients with chronic Chagas cardiomyopathy reveals a diffuse infiltrating inflammatory, hypertrophy, fibrosis and myocarditis with scarce tissue parasitism. [71][72][73] In the previous literature, the immunosuppression during the chronic phase of Chagas disease (Y strain) caused development of myocardial lesions in mice. 69 In our study, 100% of the infected animals were found to have cardiac hypertrophy and inflammatory infiltrates that were statistically different from the NEG group.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis of hearts from patients with chronic Chagas cardiomyopathy reveals a diffuse infiltrating inflammatory, hypertrophy, fibrosis and myocarditis with scarce tissue parasitism. [71][72][73] In the previous literature, the immunosuppression during the chronic phase of Chagas disease (Y strain) caused development of myocardial lesions in mice. 69 In our study, 100% of the infected animals were found to have cardiac hypertrophy and inflammatory infiltrates that were statistically different from the NEG group.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of human infection, Ferreira et al (68) conducted a microarray-based transcriptomic signature study on peripheral blood cells from Chagas disease patients, in which ex vivo transcriptional profiles were compared between patients classified in different categories: severe cardiopathy, mild cardiopathy, asymptomatic with negative PCR for T. cruzi DNA, asymptomatic with positive PCR, and control non-infected subjects. The expression of genes related to NK cells activity was found to be upregulated in positive PCR asymptomatic patients and mild cardiopathy patients, and downregulated in patients with severe cardiopathy (68).…”
Section: Innate Immunitymentioning
confidence: 99%
“…The expression of genes related to NK cells activity was found to be upregulated in positive PCR asymptomatic patients and mild cardiopathy patients, and downregulated in patients with severe cardiopathy (68). …”
Section: Innate Immunitymentioning
confidence: 99%
“…Seropositive individuals are categorized as indeterminate (C0) when they exhibit no symptoms of heart involvement, and progress through C1-C3 stages of clinical Chagas disease presented with increasing severity of structural and functional alterations in the heart [22,23]. While the indeterminate clinical form is biased towards an anti-inflammatory profile, the C1-C3 CD patients routinely present proinflammatory profile [6,[28][29][30] [6,[24][25][26] associated with a systemic increase in TNF-α + monocytes [27][28][29], oxidative stress (e.g. lipid hydroperoxides) [30,31], and an abundance of CD8 + T cells that express inflammatory cytokines and cytotoxic molecules [32].…”
Section: Plos Pathogensmentioning
confidence: 99%